Aplicação da Lei nº 13.709, de 14 de agosto de 2018 nos registros de procedimentos disciplinares relativos a servidores lotados na Universidade Federal do Espírito Santo - UFES - Pinheiro, Nathan dos Santos Kuster (2023)
Federal Universities, as public bodies with a relevant role in the scientific and socialscenarios of Brazil, need to adapt to a series of specific legislations, among them theGeneral Law for the Protection of Personal Data (LGPD) (Law nº 13.709, of 14August 2018). This regulation brings a set of mechanisms and concepts whoseapplication is of fundamental importance for the correct handling of such data. Amidstall the debates in the public and private spheres, applying security standards forstored data becomes paramount, requiring investments in employee training,software, implementation of policies and practices, with the aim of minimizing therisks of data leaks. information. The problem, when it comes to the data producedand stored on the virtual servers and computers of the Federal University of EspíritoSanto, is shown in the fact that it is not known for sure which levels of security areapplied for access, manipulation, disclosure and exclusion of these elements,specifically with regard to disciplinary procedures. Therefore, the general objective isto analyze the application of the General Law for the Protection of Personal Data indata records in Disciplinary Procedures of Ufes. The theoretical contribution wasfocused on the concepts brought by Law nº 13.709/2018, mainly with regard topersonal data, in the context of performance of the technical servers of Ufes, as datagenerators and in the advent of the LGPD, taking into account takes into account thechallenges of its implementation and improvement over time. As methodologicalprocedures, the study on screen will make use of analysis of data collected viaconsultation to electronic sites and documents related to administrative investigationsin the face of servers, as well as analysis of scientific articles and books published onthe subject analyzed. The expected result is the indication of precariousness in theprocessing of personal data in the aforementioned Ufes records, due to the lack ofdissemination of the subject in the academic community of that institution to date.Based on this information, as a technological product, a manual of good practiceswas prepared for the application of the LGPD within the scope of the FederalUniversity of Espírito Santo, paying attention to the requirements of the legislationanalyzed here, the responsibilities of the servers involved and with suggestions foruse regarding the procedures disciplinary.